The ecology of everyday things - Everard, Mark (CRC Press, an imprint of the Taylor & Francis Group, 2021)
"For many people, ecosystems may be a remote concept, yet we eat, drink, breathe and interface with them in every moment of our lives. In this engaging textbook, ecosystems scientist Dr Mark Everard considers a diversity of 'everyday things', including fascinating facts about their ecological origins : from the tea we drink, to things we wear, read and enjoy, to the ecology of communities and space flight, and the important roles played by germs and 'unappealing creatures' such as slugs and wasps. In today's society, we are so umbilically connected to ecosystems that we fail to notice them, and this oversight blinds us to the unsustainability of everyday life and the industries and policy environment that supports it. 'The Ecology of Everyday Things' takes the reader on an enlightening, fascinating voyage of discovery, all the while soundly rooted in robust science. It will stimulate awareness about how connected we all are to the natural world and its processes, and how important it is to learn to better treat our environment. Ideal for use in undergraduate and school level teaching, it will also interest, educate, engage and enthuse a wide range of less technical audiences."--Provided by publisher.